Patients´ satisfaction with the information provided before and during the orthodontic-surgical treatment - Manninen, Henriikka (My University, 2026)
Orthodontic-surgical treatment is a long process that includes initial orthodontic treatment, jaw surgery, post-operative orthodontic treatment, and retention. Patients need a lot of information from the very beginning to be able to decide whether to start treatment. Too little information can lead to, for example, unrealistic expectations and dissatisfaction with the outcome. The aim of this study was to clarify how satisfied patients, who had undergone orthodontic-surgical treatment were with the information they received before and during the treatment. This qualitative study was carried out in Turku University Hospital. Orthodontic-surgical patients in the retention phase of treatment responded to the electric REDCap-questionnaire including 24 questions. In total, five female patients responded to the study. The respondents were mainly satisfied with the information they received before and during the treatment. Nevertheless, they reported some specific issues, such as relapse or muscle tightness, about which they would have liked more information. Respondents felt that they were well listened to and actively involved in the treatment process. In comparison to previous studies, they gave a slightly more positive impression of the adequacy and quality of information. The development proposals focused on the centralization of information and the enhancement of information on treatment-related side effects. To develop patient-centred care, patient materials should be improved by evaluating what is provided and how understandable it is. It is also important to clarify how much and what type of additional information patients seek, which could support the creation of a central information source.
Keywords: information; orthodontic-surgical treatment; qualitative research; satisfaction